Bones of Contention: Curating the Work of nichola feldman-kiss. (1st October 2018) - Gewurtz, Michelle; Sinclair, Catherine
The exhibition nichola feldman-kiss: witness (2015), presented at the Ottawa Art Gallery, included between here and there (2011–15), an installation involving skeletal human remains. This reflection explores the curation of this work as a case study in the premise that exhibitions can be active agents in the construction of knowledge pertaining to polarizing issues of social justice, while balancing the curatorial role as caretaker of objects. It charts the development of the project in relation to the artist's wider practice, and the curatorial strategy of how, in light of a number of complexities, this sensitive material had to be handled with respect for object, artist and audience.